Nestin expressing progenitor cells in pulmonary vasculature - Saboor, Farhan; Justus Liebig University Giessen (My University, 2012)
Vascular wall cells distinguished by expression of the neuronal stem cell marker nestin may represent stem cell-like progenitor cells for tissues in various organs. In one of our previous studies, we found that nestin expressing vascular smooth muscle cells and pericytes in testicular blood vessels are the progenitors of testosterone producing Leydig cells. The aim of this study was to investigate nestin expression and nestin+ cells in postnatal and adult lungs.To analyze the expression pattern of nestin and its role as marker for proliferating progenitor cells in the lung, nestin expression and localization was investigated during postnatal development and vascular remodeling in a hypoxia induced pulmonary hypertension model in mice. Nestin data was compared with expression of proliferation markers (PCNA, Ki67) and PDGF receptors. Nestin expression and localization was also investigated in two rat models of pulmonary hypertension, the monocrotaline model and the Su5416/hypoxia model (VEGF receptor-2 blockage by its antagonist Sugen 5416 in combination with hypoxia) as well as in human samples from patients suffering from pulmonary hypertension and pulmonary fibrosis. Nestin was found in a subpopulation of vascular smooth muscle cells in lung vasculature. As compared to adults, significantly higher nestin expression was observed in pulmonary vasculature of postnatal lungs. While investigating the time course of postnatal development, peaks of nestin expression and vascular smooth muscle cell proliferation were found from postnatal day 3 to day 10 that reduced gradually with no nestin and vascular smooth muscle cell proliferation in adults suggesting a strong correlation between nestin expression in and proliferation of vascular smooth muscle cells. Similarly, as compared to normoxic controls, in adult lungs nestin upregulation was found between 3 days and 1 week of hypoxic exposure but not at later time points when pulmonary hypertension became clinically and histologically evident. In hypoxic lungs peak of phosphorylated (activated) PDGF receptor-ß was observed between 4 days and 1 week of hypoxic treatment. Nestin up-regulation correlated well with an increase of cell proliferation and PDGFR-ß phosphorylation/activation.Higher nestin expression was also found in vasculature of lungs from monocrotaline and Su5416/hypoxia treated rat samples. In small arteries, nestin was found in vascular smooth muscle cells. In large arteries of lungs from both rat models, in addition to vascular smooth muscle cells, nestin was also found in cells present in so-called vasculogenic zone at the border of media and adventitia. In the Su5416/hypoxia model, nestin-positive vascular smooth muscle cells were also detected in more complex lesions with neointima, a characteristic feature of this model. Along with arteries, large veins of this model also showed strong nestin immunoreactivity and interestingly, nestin+ cells in these veins were found to be cardiomyocytes.In human samples from patients of pulmonary hypertension, nestin was found in vascular smooth muscle cells in small vessels, in vasculogenic zone in large vessels as well as in vascular lesions e.g. concentric lesions, plexiform lesions and recanalization of thrombosed arteries. In lung samples from patients of pulmonary fibrosis, nestin expression was predominantly found in vascular smooth muscle cells.Certain vascular wall cells capable of proliferation could be identified by nestin expression in lungs and may be used as prognostic and diagnostic markers and new target for therapeutic interventions of diseases like pulmonary hypertension.

Es wird vermutet, dass bestimmte Blutgefäßzellen, die sich durch die Expression des neuronalen Stammzellmarkers Nestin auszeichnen, als Vorläuferzellen für den Ersatz von geschädigtem Gewebe in verschiedenen Organen dienen können. So haben frühere Studien gezeigt, dass Nestin-exprimierende glatte Muskelzellen und Perizyten von Blutgefäßen des Hodens zur Neubildung von Leydigzellen in der Lage sind. Im Rahmen dieser Doktorarbeit sollte untersucht werden, welche Rolle Nestin-exprimierende Gefäßzellen in der Lunge während der postnatalen Entwicklung und unter pathologischen Bedingungen, z. B. den bei pulmonaler Hypertonie stattfindenden Umbauvorgängen der Gefäßwand (vaskuläres Remodeling), spielen.Immunhistochemische und Immunoblot-Analysen von Mauslungen sowie Untersuchungen an GFP-Nestin-Mäusen zeigten übereinstimmend eine dramatisch höhere Nestin-Expression während der frühen postnatalen Entwicklung als in der adulten Lunge. Interessanterweise konnte ein Maximum der Nestin-Expression zwischen Tag 3 und Tag 10 postnatal festgestellt werden. Die Nestin-exprimierenden Zellen wurden als eine Subpopulation der glatten Muskelzellen charakterisiert, die zudem durch die Expression von Proliferationsmarkern (PCNA, Ki67) gekennzeichnet sind. Die Studien deuten somit auf eine bisher nicht beschriebene Rolle von Nestin-exprimierenden glatten Muskelzellen bei Proliferationsvorgängen während der postnatalen Lungenentwicklung hin. Für die Untersuchungen der Nestinexpression unter Bedingungen von pulmonaler Hypertonie wurden verschiedene Tiermodelle eingesetzt, bei denen das Krankheitsbild durch chronische Hypoxie (Maus) oder Monocrotalin (Ratte) induziert wird. Daneben konnten Lungen von Ratten genutzt werden, bei denen pulmonale Hypertonie durch eine Kombination von chronischer Hypoxie und Behandlung mit VEGF-Rezeptor2-Antagonisten (Su5416) erzeugt wurde. Hypoxie induzierte eine starke Zunahme der Nestin-Proteinexpression in Mauslungen 3 Tage nach Beginn der Behandlung, die nach weiteren 4 Tagen wieder zurückging. Die Zunahme der Nestin-Proteinexpression korrelierte mit einer Zunahme an Zellproliferation (PCNA/Ki67-positiven Zellen) und PDGF-Rezeptor ß-Aktivität (Phosphorylierung). Diese Studien weisen auf eine wesentliche und zeitlich definierbare Rolle von Nestin-exprimierenden glatten Muskelzellen beim Prozess des vaskulären Remodeling während der Entstehung von pulmonaler Hypertonie (volle Ausprägung nach 3 Wochen Hypoxie) hin. Vergleichbare Änderungen der Nestinexpression wurden auch in den beiden Rattenmodellen der pulmonalen Hypertonie gefunden. In kleinen Arterien war Nestin ausschließlich in glatten Gefäßmuskelzellen detektierbar. In großen Arterien konnte Nestin zusätzlich auch in Zellen der so genannten "vaskulogenen Zone" an der Grenze zwischen Media und Adventitia gefunden. Interessanterweise ließ sich im Su5416/Hypoxie-Modell Nestin auch in glatten Muskelzellen komplexer Läsionen mit Neointima und in großen Venen nachweisen. Deren nestinpositiven Zellen zeigten erstaunlicherweise die klassischen Merkmale von Kardiomyozyten. In menschlichen Proben von Patienten mit Lungenhypertonie wurde Nestin in glatten Gefäßmuskelzellen von kleinen Gefäßen, in vaskulogenen Zonen der großen Gefäße sowie an Stellen von Gefäßverletzungen (z. B. konzentrische Läsionen, plexiforme Läsionen) gefunden. In Lungenproben von Patienten mit Lungenfibrose war die Nestinexpression weitgehend auf glatte Gefäßmuskelzellen beschränkt.Die in dieser Arbeit erhaltenen Befunde zur Rolle von Nestin-exprimierenden Zellen bei Proliferationsvorgängen in der Lunge unter pathophysiologischen Belastungen könnten von diagnostischem Nutzen sein und die Basis für neue therapeutische Optionen darstellen.
Keywords: ddc:610